PA hot melt adhesive material for low pressure injection molding and preparation method thereof

By adding specific components to PA hot melt adhesive materials and adopting specific preparation methods, the problems of high molding shrinkage and poor mechanical properties of traditional copolyamide hot melt adhesives during low-pressure injection molding are solved, and higher melting point and mechanics are achieved Performance, reducing the forming shrinkage rate.

CN118995123BActive Publication Date: 2025-02-18SHANDONG HIGHDEV NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411497863.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-18
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

During the low-pressure injection molding process, traditional copolyamide hot melt adhesives have problems such as excessive shrinkage, easy product fall off, low production efficiency, low melting point and poor mechanical properties.

Method used

Using a PA hot melt adhesive material including carboxylic acid monomer, suberic acid, hexanediamine, dodecanediamine, paraffin, benzoic acid, free radical initiator and functional filler, it can be improved by a specific preparation method. Melting point and mechanical properties.

Benefits of technology

It improves the melting point and mechanical properties of PA hot melt adhesive materials, reduces the molding shrinkage rate, and enhances the stability and production efficiency of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of adhesives, and specifically discloses a PA hot melt adhesive material for low-pressure injection molding and a preparation method thereof. The PA hot melt adhesive material comprises the following raw materials in parts by weight: 270-320 parts of carboxylic acid monomers, 50-60 parts of suberic acid, 72-116 parts of hexamethylenediamine, 18-36 parts of dodecanediamine, 1.2-1.6 parts of paraffin wax, 0.3-0.4 parts of benzoic acid and 4-7 parts of functional fillers. The invention adds carboxylic acid monomers and functional fillers into the hot melt adhesive, wherein the carboxylic acid monomers contain abundant active hydroxyl groups, benzene rings, flexible long-chain alkane structures and unsaturated double bonds, and can not only be cured and cross-linked with long-chain carboxylic acids in a base material, but also react with the functional fillers, thereby improving the overall cross-linking density of the hot melt adhesive system, improving the waterproof performance of the hot melt adhesive, improving the melting point and mechanical properties of the hot melt adhesive material, and reducing the molding shrinkage rate thereof.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of adhesives, and more specifically, to a PA hot melt adhesive material used for low-pressure injection molding and a preparation method thereof. Background Art

[0002] Copolyamide hot melt adhesive has the characteristics of fast hot melt curing, strong initial adhesion, solvent resistance, water resistance, and high temperature resistance, and has broad application prospects.

[0003] However, during the low-pressure injection molding process, traditional copolyamide hot melt adhesives may cause the product to fall off due to excessive molding shrinkage; and a longer open time will increase the time required for adhesive application and reduce production efficiency.

[0004] In addition, the preparation process of copolyamide hot melt adhesive has the problem of low melting point. In the prior art, conventional additives and inorganic fillers are often added to improve its performance. However, conventional additives cannot participate in the curing reaction and are easy to migrate and precipitate. The compatibility of inorganic fillers with copolyamide hot melt adhesive is poor, which results in that the melting point of the prepared hot melt adhesive is not significantly improved, but the mechanical properties of the prepared hot melt adhesive are poor. In addition, the existing copolyamide hot melt adhesive has the problem of poor flexibility at low temperature. Therefore, providing a PA hot melt adhesive material with high melting point, low molding shrinkage and good mechanical properties and a preparation method thereof is a technical problem that needs to be solved at present. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a PA hot melt adhesive material for low-pressure injection molding and a preparation method thereof.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] A PA hot melt adhesive material for low-pressure injection molding, comprising the following raw materials in parts by weight: 270-320 parts of carboxylic acid monomer, 50-60 parts of suberic acid, 72-116 parts of hexamethylenediamine, 18-36 parts of dodecanediamine, 1.2-1.6 parts of paraffin wax, 0.3-0.4 parts of benzoic acid, 5.4-6.2 parts of free radical initiator and 4-7 parts of functionalized filler;

[0008] The preparation method of the PA hot melt adhesive material used for low-pressure injection molding comprises the following steps:

[0009] Step S1, preparation of prepolymer: carboxylic acid monomer, suberic acid, hexamethylenediamine, dodecanediamine and 2 / 3 parts by weight of free radical initiator are uniformly mixed, heated to 62-64° C., stirred for reaction for 2-3 hours to obtain an acid-amine mixture, and continued to heat to 136-144° C., polycondensation reaction for 0.6-1.6 hours to obtain a prepolymer;

[0010] Step S2, preparation of hot melt adhesive material: add paraffin and benzoic acid to the prepolymer prepared in step S1, stir evenly, continue to heat to 239-245°C, continue stirring and reacting for 0.8-1.4h, cool to 55-65°C, add the remaining mass part of free radical initiator, then add functional filler, continue stirring for 2.4-3.2h, cool, and granulate to obtain PA hot melt adhesive material for low-pressure injection molding.

[0011] Preferably, the free radical initiator is azobisisobutyronitrile or azobisisoheptanenitrile.

[0012] Preferably, the carboxylic acid monomer is prepared by the following steps:

[0013] Step A1, under nitrogen protection, add the esterification monomer and undecylenic acid to anhydrous tetrahydrofuran, stir evenly, heat to 35-45 ° C, and add p-toluenesulfonic acid and anhydrous tetrahydrofuran mixed solution a while stirring, and control the dripping within 10 minutes. After the dripping is completed, continue to stir for 3-5 hours, then heat to reflux, continue to stir and react for 8-12 hours. After the reaction is completed, filter with suction, wash and dry the filter cake to obtain an unsaturated monomer, wherein the mass ratio of the esterification monomer, undecylenic acid, anhydrous tetrahydrofuran and the mixed solution a is 1.5-2.3:1:30-40:18-22, and the mass ratio of p-toluenesulfonic acid and anhydrous tetrahydrofuran in the mixed solution a is 0.2-0.6:22-26. In the above process, the esterification monomer and undecylenic acid undergo esterification reaction to obtain an unsaturated monomer, and the structural formula of the unsaturated monomer is as follows:

[0014]

[0015] Step A2, adding unsaturated monomer, 2,2-dimethylsuccinic anhydride and 4-dimethylaminopyridine to anhydrous tetrahydrofuran, stirring evenly, heating to reflux, continuing stirring to react for 16-20h, then adding a mixed solution b of deionized water and anhydrous tetrahydrofuran, then adding dichloromethane, washing, rotary evaporation, and drying to obtain a carboxylic acid monomer, wherein the unsaturated monomer, 2,2-dimethylsuccinic anhydride, 4-dimethylaminopyridine, anhydrous tetrahydrofuran, the mixed solution b and dichloromethane are The mass ratio of alkane is 1.2-1.4:3.6-4.2:0.1-0.14:45-55:18-22:6-10. In the mixed solution b, the mass ratio of deionized water and anhydrous tetrahydrofuran is 6-10:16-20. In the above reaction process, 4-dimethylaminopyridine is used as a catalyst, and the hydroxyl group on the unsaturated monomer undergoes a ring-opening esterification reaction with 2,2-dimethylsuccinic anhydride to obtain a carboxylic acid monomer. The structural formula of the carboxylic acid monomer is as follows:

[0016]

[0017] Preferably, the esterification monomer is prepared by the following steps:

[0018] 3,5-diaminobenzoic acid, pentaerythritol allyl ether and p-toluenesulfonic acid are added to anhydrous N,N-dimethylformamide (DMF), stirred evenly, heated to 75-85°C under nitrogen protection, stirred and reacted for 18-20 hours, and after the reaction is completed, allowed to stand for 4-6 hours, filtered, and the filter cake is washed and dried to obtain an esterification monomer, wherein the mass ratio of 3,5-diaminobenzoic acid, pentaerythritol allyl ether, p-toluenesulfonic acid and anhydrous DMF is 1:2-3:0.06-0.08:35-45. In the above reaction process, anhydrous DMF is used as solvent and p-toluenesulfonic acid is used as catalyst, and 3,5-diaminobenzoic acid and pentaerythritol allyl ether undergo esterification reaction to obtain an esterification monomer. The structural formula of the esterification monomer is as follows:

[0019]

[0020] In the above reaction process, the amount of pentaerythritol allyl ether is controlled to be slightly higher than 3,5-diaminobenzoic acid, so that after the reaction is completed, there are still remaining hydroxyl groups that can undergo subsequent reactions.

[0021] Preferably, the functionalized filler is prepared by the following steps:

[0022] Step B1, 4,4'-diaminodiphenyl disulfide, deionized water, anhydrous ethanol and KH-560 are mixed evenly, heated to 76-80°C, stirred and reacted for 10-14h, centrifuged, precipitated, washed and dried to obtain an amino monomer, wherein the mass ratio of 4,4'-diaminodiphenyl disulfide, deionized water, anhydrous ethanol and KH-560 is 1.2-1.8:10:20-24:0.8-1.0. During the above reaction process, the amino group on 4,4'-diaminodiphenyl disulfide and the epoxy group on KH-560 undergo a ring-opening reaction to obtain an amino monomer;

[0023] Step B2, adding the amino monomer to anhydrous DMF, heating to 45-55°C, stirring evenly, adjusting the pH to 9-10, and dripping a mixed solution c of octadecenyl succinic anhydride and isopropanol while stirring, and controlling the dripping to be completed within 30 minutes. After the dripping is completed, heating to 74-80°C, continuing to stir and react for 6-10 hours, adjusting the pH to neutral, and obtaining a modified solution, wherein the mass ratio of the amino monomer, anhydrous DMF and the mixed solution c is 2-4:50-60:16, and the mass ratio of octadecenyl succinic anhydride and isopropanol in the mixed solution c is 0.6-1.2:12. In the above reaction process, using anhydrous DMF as a solvent, the amino group on the amino monomer undergoes a ring-opening esterification reaction with octadecenyl succinic anhydride to obtain a modified solution containing a modifier;

[0024] Step B3, ultrasonically disperse the nano-silicon dioxide in anhydrous DMF, add the modifying liquid and deionized water, heat to 55-65°C, stir and react for 4-5h, filter, wash, and dry to obtain a functionalized filler, wherein the mass ratio of the nano-silicon dioxide, anhydrous DMF, modifying liquid and deionized water is 6-8:65-75:16-24:8-10. During the above reaction process, the product obtained by hydrolysis of the modifying liquid undergoes a condensation reaction with the surface hydroxyl groups of the nano-silicon dioxide to obtain a functionalized filler with rich surface carboxyl groups and disulfide bonds.

[0025] In summary, the present invention has the following beneficial effects: in order to improve the melting point and mechanical properties of PA hot melt adhesive materials and reduce their molding shrinkage, the present invention starts from two aspects. First, a carboxylic acid monomer is added to the PA hot melt adhesive material. The carboxylic acid monomer contains rich active amino groups, benzene rings, flexible long-chain alkane structures and unsaturated double bonds. On the one hand, the active amino group can undergo curing and cross-linking with the long-chain carboxylic acid in the base material to improve the cross-linking degree of the hot melt adhesive material, strengthen the intermolecular bonding force, and improve the mechanical properties of the hot melt adhesive material. On the other hand, as an anchor point, it undergoes an amidation reaction with the carboxyl group on the functional filler to further improve the cross-linking degree and the mechanical properties of the hot melt adhesive material. The presence of the benzene ring can exert its own rigid structure, improve the melting point of the hot melt adhesive material, and reduce its molding shrinkage. The unsaturated double bonds Due to the presence of the flexible long-chain alkane structure, the flexible structure in the base material and the functional filler can be entangled to form a mutually entangled molecular interpenetrating network structure, further improving the mechanical properties of the hot melt adhesive material. The presence of unsaturated double bonds can chemically bond the double bond structure on the carboxylic acid monomer and the functional filler, thereby improving the compatibility of the functional filler and further improving the mechanical properties of the hot melt adhesive material. Secondly, the addition of functional fillers, on the one hand, can bring into play the good mechanical properties of nano-silica and thus improve the melting point and mechanical properties of the hot melt adhesive. On the other hand, the modifier grafted on the surface of the functional filler has a flexible long-chain structure and a disulfide bond and good flexibility. When introduced into the hot melt adhesive material, it can work synergistically with the carboxylic acid monomer to jointly improve the melting point and mechanical properties of the hot melt adhesive material and reduce its molding shrinkage. DETAILED DESCRIPTION

[0026] In order to make the embodiments of the present invention easier to understand, the present invention will be described in detail below with reference to specific examples. These examples are only for illustration and are not intended to limit the scope of application of the present invention.

[0027] The contents of the main raw materials and their components used in the examples are as follows:

[0028] Paraffin wax is semi-refined paraffin wax produced by Hubei Xinghengye Technology Co., Ltd., with CAS number 8002-74-2.

[0029] Preparation Examples 1-3 and Comparative Preparation Example 1 provide methods for preparing esterification monomers.

[0030] Preparation Example 1

[0031] The esterification monomer is prepared by the following steps:

[0032] 3,5-diaminobenzoic acid, pentaerythritol allyl ether and p-toluenesulfonic acid were added to anhydrous DMF, and the mixture was stirred at a speed of 500 rpm for 0.6 h until uniform. Under nitrogen protection, the temperature was raised to 75°C, the speed was maintained unchanged, and the reaction was stirred for 18 h. After the reaction was completed, the mixture was allowed to stand for 4 h, filtered, and the filter cake was washed with anhydrous ethanol and deionized water for 3 times, and dried at 60°C to constant weight to obtain an esterification monomer, wherein the mass ratio of 3,5-diaminobenzoic acid, pentaerythritol allyl ether, p-toluenesulfonic acid and anhydrous DMF was 1:2:0.06:35.

[0033] Preparation Example 2

[0034] The esterification monomer is prepared by the following steps:

[0035] 3,5-diaminobenzoic acid, pentaerythritol allyl ether and p-toluenesulfonic acid were added to anhydrous DMF, and the mixture was stirred at a speed of 550 rpm for 0.5 h until uniform. Under nitrogen protection, the temperature was raised to 80°C, the speed was maintained unchanged, and the reaction was stirred for 19 h. After the reaction was completed, the mixture was allowed to stand for 5 h, filtered, and the filter cake was washed with anhydrous ethanol and deionized water for 4 times, and dried at 65°C to constant weight to obtain an esterification monomer, wherein the mass ratio of 3,5-diaminobenzoic acid, pentaerythritol allyl ether, p-toluenesulfonic acid and anhydrous DMF was 1:2.5:0.07:40.

[0036] Preparation Example 3

[0037] The esterification monomer is prepared by the following steps:

[0038] 3,5-diaminobenzoic acid, pentaerythritol allyl ether and p-toluenesulfonic acid were added to anhydrous DMF, and the mixture was stirred at a speed of 600 rpm for 0.6 h until uniform. Under nitrogen protection, the temperature was raised to 85°C, the speed was maintained constant, and the reaction was stirred for 20 h. After the reaction was completed, the mixture was allowed to stand for 6 h, filtered, and the filter cake was washed with anhydrous ethanol and deionized water for 5 times, and dried at 70°C to constant weight to obtain an esterification monomer, wherein the mass ratio of 3,5-diaminobenzoic acid, pentaerythritol allyl ether, p-toluenesulfonic acid and anhydrous DMF was 1:3:0.08:45.

[0039] Comparative Preparation Example 1

[0040] The esterification monomer is prepared by the following steps:

[0041] Glycine, pentaerythritol allyl ether and p-toluenesulfonic acid were added to anhydrous DMF, and the mixture was stirred at a speed of 500 rpm for 0.6 h until uniform. Under nitrogen protection, the temperature was raised to 75°C, the speed was maintained constant, and the reaction was stirred for 18 h. After the reaction was completed, the mixture was allowed to stand for 4 h, filtered, and the filter cake was washed with anhydrous ethanol and deionized water for 3 times, and dried at 60°C to constant weight to obtain an esterification monomer, wherein the mass ratio of glycine, pentaerythritol allyl ether, p-toluenesulfonic acid and anhydrous DMF was 1:2:0.06:35.

[0042] Preparation Examples 4-6 and Comparative Preparation Examples 2-3 provide methods for preparing carboxylic acid monomers.

[0043] Preparation Example 4

[0044] The carboxylic acid monomer is prepared by the following steps:

[0045] Step A1, under nitrogen protection, the esterification monomer and undecylenic acid prepared in Preparation Example 1 are added to anhydrous tetrahydrofuran, the speed is controlled to be 450rpm and stirred for 0.45h until uniform, the temperature is raised to 35°C, and p-toluenesulfonic acid and anhydrous tetrahydrofuran are added dropwise to the mixed solution a while stirring, and the dripping is controlled within 10min. After the dripping is completed, stirring is continued for 3h, and then the temperature is raised to reflux, the speed is maintained unchanged, and the stirring reaction is continued for 8h. After the reaction is completed, suction filtration is performed, and the filter cake is washed 3 times with anhydrous ethanol and deionized water, and dried at 60°C to constant weight to obtain an unsaturated monomer, wherein the mass ratio of the esterification monomer, undecylenic acid, anhydrous tetrahydrofuran and the mixed solution a is 1.5:1:30:18, and the mass ratio of p-toluenesulfonic acid and anhydrous tetrahydrofuran in the mixed solution a is 0.2:22;

[0046] Step A2, the unsaturated monomer, 2,2-dimethylsuccinic anhydride and 4-dimethylaminopyridine are added to anhydrous tetrahydrofuran, the speed is controlled to be 700rpm and stirred for 0.5h until uniform, the temperature is raised to reflux, the speed is maintained unchanged, and the stirring reaction is continued for 16h, and then a mixed solution b of deionized water and anhydrous tetrahydrofuran is added, and then dichloromethane is added, and the mixture is washed with anhydrous ethanol and deionized water three times in sequence, and the deionized water and anhydrous tetrahydrofuran are removed by rotary evaporation, and the rotary evaporation temperature is controlled to be 55°C, and the mixture is dried to constant weight at 65°C to obtain a carboxylic acid monomer, wherein the mass ratio of the unsaturated monomer, 2,2-dimethylsuccinic anhydride, 4-dimethylaminopyridine, anhydrous tetrahydrofuran, the mixed solution b and dichloromethane is 1.2:3.6:0.1:45:18:6, and the mass ratio of deionized water and anhydrous tetrahydrofuran in the mixed solution b is 6:16.

[0047] Preparation Example 5

[0048] The carboxylic acid monomer is prepared by the following steps:

[0049] Step A1, under nitrogen protection, the esterification monomer and undecylenic acid prepared in Preparation Example 2 are added to anhydrous tetrahydrofuran, the speed is controlled to be 500rpm and stirred for 0.40h until uniform, the temperature is raised to 40°C, and p-toluenesulfonic acid and anhydrous tetrahydrofuran are added dropwise to the mixed solution a while stirring, and the dripping is controlled within 10min. After the dripping is completed, the speed is maintained unchanged, and stirring is continued for 4h, and then the temperature is raised to reflux, and the stirring reaction is continued for 10h. After the reaction is completed, suction filtration is performed, and the filter cake is washed 4 times with anhydrous ethanol and deionized water, and dried at 65°C to constant weight to obtain an unsaturated monomer, wherein the mass ratio of the esterification monomer, undecylenic acid, anhydrous tetrahydrofuran and the mixed solution a is 1.8:1:35:20, and the mass ratio of p-toluenesulfonic acid and anhydrous tetrahydrofuran in the mixed solution a is 0.4:24;

[0050] Step A2, the unsaturated monomer, 2,2-dimethylsuccinic anhydride and 4-dimethylaminopyridine are added to anhydrous tetrahydrofuran, the speed is controlled to be 750rpm and stirred for 0.4h until uniform, the temperature is raised to reflux, the speed is maintained unchanged, and the stirring reaction is continued for 18h, and then a mixed solution b of deionized water and anhydrous tetrahydrofuran is added, and then dichloromethane is added, and the mixture is washed with anhydrous ethanol and deionized water 4 times in sequence, and the deionized water and anhydrous tetrahydrofuran are removed by rotary evaporation, and the rotary evaporation temperature is controlled to be 60°C, and the mixture is dried to constant weight at 70°C to obtain a carboxylic acid monomer, wherein the mass ratio of the unsaturated monomer, 2,2-dimethylsuccinic anhydride, 4-dimethylaminopyridine, anhydrous tetrahydrofuran, the mixed solution b and dichloromethane is 1.3:3.9:0.12:50:20:8, and the mass ratio of deionized water and anhydrous tetrahydrofuran in the mixed solution b is 8:18.

[0051] Preparation Example 6

[0052] The carboxylic acid monomer is prepared by the following steps:

[0053] Step A1, under nitrogen protection, the esterification monomer and undecylenic acid prepared in Preparation Example 3 are added to anhydrous tetrahydrofuran, the rotation speed is controlled to be 550rpm and stirred for 0.35h until uniform, the temperature is raised to 65°C, and sodium methoxide, methanol, deionized water and anhydrous tetrahydrofuran are added dropwise to a mixed solution a while stirring, and the dripping is controlled within 10min. After the dripping is completed, the rotation speed is maintained unchanged, and stirring is continued for 5h, and then the temperature is raised to reflux, and the stirring reaction is continued for 12h. After the reaction is completed, methanol and anhydrous tetrahydrofuran are removed by rotary evaporation, the rotary evaporation temperature is controlled to be 60°C, and then recrystallized 4 times, and dried at 70°C to constant weight to obtain an unsaturated monomer, wherein the mass ratio of the esterification monomer, undecylenic acid, anhydrous tetrahydrofuran and the mixed solution a is 2.3:1:40:22, and the mass ratio of p-toluenesulfonic acid and anhydrous tetrahydrofuran in the mixed solution a is 0.6:26;

[0054] Step A2, the unsaturated monomer, 2,2-dimethylsuccinic anhydride and 4-dimethylaminopyridine are added to anhydrous tetrahydrofuran, the speed is controlled to be 800rpm and stirred for 0.3h until uniform, the temperature is raised to reflux, the speed is maintained unchanged, and the stirring reaction is continued for 20h, and then a mixed solution b of deionized water and anhydrous tetrahydrofuran is added, and then dichloromethane is added, and the mixture is washed with anhydrous ethanol and deionized water 5 times in sequence, and the deionized water and anhydrous tetrahydrofuran are removed by rotary evaporation, and the rotary evaporation temperature is controlled to be 65°C, and the mixture is dried to constant weight at 75°C to obtain a carboxylic acid monomer, wherein the mass ratio of the unsaturated monomer, 2,2-dimethylsuccinic anhydride, 4-dimethylaminopyridine, anhydrous tetrahydrofuran, the mixed solution b and dichloromethane is 1.4:4.2:0.14:55:22:10, and the mass ratio of deionized water and anhydrous tetrahydrofuran in the mixed solution b is 10:20.

[0055] Comparative Preparation Example 2

[0056] The carboxylic acid monomer is prepared by the following steps:

[0057] Step A1, under nitrogen protection, the esterification monomer and undecylenic acid prepared in Comparative Preparation Example 1 were added to anhydrous tetrahydrofuran, the speed was controlled to be 450rpm and stirred for 0.45h until uniform, the temperature was raised to 45°C, and p-toluenesulfonic acid and anhydrous tetrahydrofuran were added dropwise to the mixed solution a while stirring, and the dripping was controlled within 10min. After the dripping was completed, stirring was continued for 3h, and then the temperature was raised to reflux, the speed was maintained unchanged, and the stirring reaction was continued for 8h. After the reaction was completed, the filter cake was filtered, and the filter cake was washed 3 times with anhydrous ethanol and deionized water, and dried at 60°C to constant weight to obtain an unsaturated monomer, wherein the mass ratio of the esterification monomer, undecylenic acid, anhydrous tetrahydrofuran and the mixed solution a was 1.5:1:30:18, and the mass ratio of p-toluenesulfonic acid and anhydrous tetrahydrofuran in the mixed solution a was 0.2:22;

[0058] Step A2, the unsaturated monomer, 2,2-dimethylsuccinic anhydride and 4-dimethylaminopyridine are added to anhydrous tetrahydrofuran, the speed is controlled to be stirred at 700rpm for 0.5h until uniform, the temperature is raised to 62°C, the speed is maintained unchanged, and the stirring reaction is continued for 16h, and then a mixed solution b of deionized water and anhydrous tetrahydrofuran is added, and then dichloromethane is added, and the mixture is washed with anhydrous ethanol and deionized water three times in sequence, and the deionized water and anhydrous tetrahydrofuran are removed by rotary evaporation, the rotary evaporation temperature is controlled to be 55°C, and the mixture is dried to constant weight at 65°C to obtain a carboxylic acid monomer, wherein the mass ratio of the unsaturated monomer, 2,2-dimethylsuccinic anhydride, 4-dimethylaminopyridine, anhydrous tetrahydrofuran, the mixed solution b and dichloromethane is 1.2:3.6:0.1:45:18:6, and the mass ratio of deionized water and anhydrous tetrahydrofuran in the mixed solution b is 6:16.

[0059] Comparative Preparation Example 3

[0060] The carboxylic acid monomer is prepared by the following steps:

[0061] Step A1, under nitrogen protection, add the esterification monomer and acrylic acid prepared in Preparation Example 1 to anhydrous tetrahydrofuran, control the speed to 450rpm and stir for 0.45h until uniform, heat to 35°C, and add p-toluenesulfonic acid and anhydrous tetrahydrofuran mixed solution a dropwise while stirring, control the dripping to be completed within 10min, and continue stirring for 3h, then heat to reflux, maintain the speed unchanged, continue stirring to react for 8h, and after the reaction is completed, filter with suction, wash the filter cake with anhydrous ethanol and deionized water 3 times, and dry at 60°C to constant weight to obtain an unsaturated monomer, wherein the mass ratio of the esterification monomer, acrylic acid, anhydrous tetrahydrofuran and mixed solution a is 1.5:1:30:18, and the mass ratio of p-toluenesulfonic acid and anhydrous tetrahydrofuran in the mixed solution a is 0.2:22;

[0062] Step A2, the unsaturated monomer, 2,2-dimethylsuccinic anhydride and 4-dimethylaminopyridine are added to anhydrous tetrahydrofuran, the speed is controlled to be 700rpm and stirred for 0.5h until uniform, the temperature is raised to reflux, the speed is maintained unchanged, and the stirring reaction is continued for 16h, and then a mixed solution b of deionized water and anhydrous tetrahydrofuran is added, and then dichloromethane is added, and the mixture is washed with anhydrous ethanol and deionized water three times in sequence, and the deionized water and anhydrous tetrahydrofuran are removed by rotary evaporation, and the rotary evaporation temperature is controlled to be 55°C, and the mixture is dried to constant weight at 65°C to obtain a carboxylic acid monomer, wherein the mass ratio of the unsaturated monomer, 2,2-dimethylsuccinic anhydride, 4-dimethylaminopyridine, anhydrous tetrahydrofuran, the mixed solution b and dichloromethane is 1.2:3.6:0.1:45:18:6, and the mass ratio of deionized water and anhydrous tetrahydrofuran in the mixed solution b is 6:16.

[0063] Preparation Examples 7-9 and Comparative Preparation Examples 4-5 provide methods for preparing functionalized fillers.

[0064] Preparation Example 7

[0065] The functionalized filler is prepared by the following steps:

[0066] Step B1, 4,4'-diaminodiphenyl disulfide, deionized water, anhydrous ethanol and KH-560 were stirred at a speed of 600 rpm for 0.55 h until uniform, the temperature was raised to 76 ° C, the speed was maintained unchanged, and the stirring reaction was continued for 10 h, centrifuged, and the precipitate was washed with deionized water 3 times, and then dried at 65 ° C to constant weight to obtain an amino monomer, wherein the mass ratio of 4,4'-diaminodiphenyl disulfide, deionized water, anhydrous ethanol and KH-560 was 1.2:10:20:0.8;

[0067] Step B2, adding the amino monomer to anhydrous DMF, heating to 45°C, stirring at a speed of 400 rpm for 0.6h until uniform, then adjusting the pH to 9 with a 0.6M sodium hydroxide aqueous solution, adding dropwise a mixed solution c of octadecenyl succinic anhydride and isopropanol while stirring, and controlling the dripping to be completed within 30min. After the dripping is completed, heating to 74°C, maintaining the speed unchanged, and continuing to stir and react for 6h, adjusting the pH to neutral with a 0.5M hydrochloric acid aqueous solution to obtain a modified solution, wherein the mass ratio of the amino monomer, anhydrous DMF and the mixed solution c is 2:50:16, and the mass ratio of octadecenyl succinic anhydride and isopropanol in the mixed solution c is 0.6:12;

[0068] Step B3, ultrasonically disperse the nano-silica in anhydrous DMF, control the ultrasonic frequency to 40kHz, the ultrasonic power to 600w, the ultrasonic for 0.5min, add the modifying liquid and deionized water, raise the temperature to 55°C, control the speed to 550rpm and stir for 4h, filter, wash the filter cake with anhydrous ethanol and deionized water for 3 times, and dry at 50°C to constant weight to obtain a functionalized filler, wherein the mass ratio of nano-silica, anhydrous DMF, modifying liquid and deionized water is 6:65:16:8.

[0069] Preparation Example 8

[0070] The functionalized filler is prepared by the following steps:

[0071] Step B1, 4,4'-diaminodiphenyl disulfide, deionized water, anhydrous ethanol and KH-560 were stirred at a speed of 700 pm for 0.50 h until uniform, the temperature was raised to 78 ° C, the speed was maintained unchanged, the stirring reaction was continued for 12 h, centrifuged, the precipitate was washed 4 times with deionized water, and then dried at 70 ° C to constant weight to obtain an amino monomer, wherein the mass ratio of 4,4'-diaminodiphenyl disulfide, deionized water, anhydrous ethanol and KH-560 was 1.5:10:22:0.9;

[0072] Step B2, adding the amino monomer to anhydrous DMF, heating to 50°C, stirring at a speed of 500 rpm for 0.5h until uniform, then adjusting the pH to 9.5 with a 0.8M sodium hydroxide aqueous solution, adding dropwise a mixed solution c of octadecenyl succinic anhydride and isopropanol while stirring, and controlling the dripping to be completed within 30min. After the dripping is completed, heating to 76°C, maintaining the speed unchanged, continuing to stir and react for 8h, adjusting the pH to neutral, and obtaining a modified solution, wherein the mass ratio of the amino monomer, anhydrous DMF and the mixed solution c is 3:55:16, and the mass ratio of octadecenyl succinic anhydride and isopropanol in the mixed solution c is 0.9:12;

[0073] Step B3, ultrasonically disperse the nano-silica in anhydrous DMF, control the ultrasonic frequency to 35kHz, the ultrasonic power to 550w, and ultrasonicate for 0.55h, add the modifying liquid and deionized water, raise the temperature to 60°C, control the speed to 600rpm and stir the reaction for 4.5h, filter, wash the filter cake with anhydrous ethanol and deionized water 4 times, and dry it at 55°C to constant weight to obtain a functionalized filler, wherein the mass ratio of nano-silica, anhydrous DMF, modifying liquid and deionized water is 7:70:20:9.

[0074] Preparation Example 9

[0075] The functionalized filler is prepared by the following steps:

[0076] Step B1, 4,4'-diaminodiphenyl disulfide, deionized water, anhydrous ethanol and KH-560 were stirred at a speed of 800 rpm for 0.45 h until uniform, the temperature was raised to 80 ° C, and the stirring reaction was continued for 14 h, centrifuged, and the precipitate was washed with deionized water 5 times, and then dried at 75 ° C to constant weight to obtain an amino monomer, wherein the mass ratio of 4,4'-diaminodiphenyl disulfide, deionized water, anhydrous ethanol and KH-560 was 1.8:10:24:1.0;

[0077] Step B2, adding the amino monomer to anhydrous DMF, heating to 55°C, stirring at a speed of 600 rpm for 0.4h until uniform, then adjusting the pH to 10.0 with a 1.0M sodium hydroxide aqueous solution, adding dropwise a mixed solution c of octadecenyl succinic anhydride and isopropanol while stirring, and controlling the dripping to be completed within 30min. After the dripping is completed, heating to 80°C, maintaining the speed unchanged, continuing to stir and react for 10h, adjusting the pH to neutral, and obtaining a modified solution, wherein the mass ratio of the amino monomer, anhydrous DMF and the mixed solution c is 4:60:16, and the mass ratio of octadecenyl succinic anhydride and isopropanol in the mixed solution c is 1.2:12;

[0078] Step B3, ultrasonically disperse the nano-silica in anhydrous DMF, control the ultrasonic frequency to 30kHz, the ultrasonic power to 500w, and the ultrasonic treatment for 0.60h, add the modifying liquid and deionized water, raise the temperature to 65°C, control the speed to 600rpm and stir the reaction for 5h, filter, wash the filter cake with anhydrous ethanol and deionized water 5 times, and dry at 60°C to constant weight to obtain a functionalized filler, wherein the mass ratio of nano-silica, anhydrous DMF, modifying liquid and deionized water is 8:75:24:10.

[0079] Comparative Preparation Example 4

[0080] The functionalized filler is prepared by the following steps:

[0081] Step B1, 4,4'-diaminobenzophenone, deionized water, anhydrous ethanol and KH-560 were stirred at a speed of 600 rpm for 0.55 h until uniform, the temperature was raised to 76 ° C, the speed was maintained unchanged, and the stirring reaction was continued for 10 h, centrifuged, and the precipitate was washed with deionized water 3 times, and then dried at 65 ° C to constant weight to obtain an amino monomer, wherein the mass ratio of 4,4'-diaminobenzophenone, deionized water, anhydrous ethanol and KH-560 was 1.2:10:20:0.8;

[0082] Step B2, adding the amino monomer to anhydrous DMF, heating to 45°C, stirring at a speed of 400 rpm for 0.6h until uniform, then adjusting the pH to 9 with a 0.6M sodium hydroxide aqueous solution, adding a mixed solution b of octadecenyl succinic anhydride and isopropanol dropwise while stirring, and controlling the dripping to be completed within 30min. After the dripping is completed, heating to 74°C, maintaining the speed unchanged, and continuing to stir and react for 6h, adjusting the pH to neutral with a 0.5M hydrochloric acid aqueous solution to obtain a modified solution, wherein the mass ratio of the amino monomer, anhydrous DMF and the mixed solution b is 2:50:16, and the mass ratio of octadecenyl succinic anhydride and isopropanol in the mixed solution b is 0.6:12;

[0083] Step B3, ultrasonically disperse the nano-silica in anhydrous DMF, control the ultrasonic frequency to 40kHz, the ultrasonic power to 600w, the ultrasonic for 0.5min, add the modifying liquid and deionized water, raise the temperature to 55°C, control the speed to 550rpm and stir for 4h, filter, wash the filter cake with anhydrous ethanol and deionized water for 3 times, and dry at 50°C to constant weight to obtain a functionalized filler, wherein the mass ratio of nano-silica, anhydrous DMF, modifying liquid and deionized water is 6:65:16:8.

[0084] Comparative Preparation Example 5

[0085] The functionalized filler is prepared by the following steps:

[0086] Step B1, 4,4'-diaminodiphenyl disulfide, deionized water, anhydrous ethanol and KH-560 were stirred at a speed of 600 rpm for 0.55 h until uniform, the temperature was raised to 76 ° C, the speed was maintained unchanged, and the stirring reaction was continued for 10 h, centrifuged, and the precipitate was washed with deionized water 3 times, and then dried at 65 ° C to constant weight to obtain an amino monomer, wherein the mass ratio of 4,4'-diaminodiphenyl disulfide, deionized water, anhydrous ethanol and KH-560 was 1.2:10:20:0.8;

[0087] Step B2, adding the amino monomer to anhydrous DMF, heating to 45°C, controlling the speed to be 400rpm and stirring for 0.6h until uniform, then adjusting the pH to 9 with 0.6M sodium hydroxide aqueous solution, adding dropwise the mixed solution b of itaconic anhydride and isopropanol while stirring, and controlling the dripping to be completed within 30min. After the dripping is completed, heating to 74°C, maintaining the speed unchanged, continuing to stir and react for 6h, and adjusting the pH to neutral with 0.5M hydrochloric acid aqueous solution to obtain a modified solution, wherein the mass ratio of the amino monomer, anhydrous DMF and the mixed solution b is 2:50:16, and the mass ratio of itaconic anhydride and isopropanol in the mixed solution b is 0.6:12;

[0088] Step B3, ultrasonically disperse the nano-silica in anhydrous DMF, control the ultrasonic frequency to 40kHz, the ultrasonic power to 600w, the ultrasonic for 0.5min, add the modifying liquid and deionized water, raise the temperature to 55°C, control the speed to 550rpm and stir for 4h, filter, wash the filter cake with anhydrous ethanol and deionized water for 3 times, and dry at 50°C to constant weight to obtain a functionalized filler, wherein the mass ratio of nano-silica, anhydrous DMF, modifying liquid and deionized water is 6:65:16:8.

[0089] Examples 1-3 and Comparative Examples 1-3 provide a PA hot melt adhesive material for low-pressure injection molding and a preparation method thereof.

[0090] Example 1

[0091] This embodiment provides a PA hot melt adhesive material for low-pressure injection molding, comprising the following raw materials in parts by weight: 270 parts of carboxylic acid monomer prepared in Preparation Example 4, 50 parts of suberic acid, 72 parts of hexamethylenediamine, 18 parts of dodecanediamine, 1.2 parts of paraffin, 0.3 parts of benzoic acid, 5.4 parts of azobisisobutyronitrile and 4 parts of functional filler prepared in Preparation Example 7;

[0092] The preparation method of the PA hot melt adhesive material used for low-pressure injection molding comprises the following steps:

[0093] Step S1, preparation of prepolymer: carboxylic acid monomer, suberic acid, hexamethylenediamine, dodecanediamine and 2 / 3 parts by weight of azobisisobutyronitrile were stirred at a speed of 750 rpm for 0.45 h until uniform, heated to 62° C., maintained at a constant speed, stirred for reaction for 2 h to obtain an acid-amine mixture, and continued to heat to 136° C., maintained at a constant speed, and polycondensed for 0.6 h to obtain a prepolymer;

[0094] Step S2, preparation of hot melt adhesive material: paraffin and benzoic acid are added to the prepolymer prepared in step S1, and the speed is controlled to be stirred at 820 rpm for 0.6 h until uniform, and the temperature is continued to rise to 239 ° C., the speed is maintained unchanged, and the reaction is stirred for 0.8 h. The temperature is lowered to 55 ° C., the remaining mass parts of azobisisobutyronitrile are added, and then the functional filler is added. The stirring is continued for 2.4 h, cooled, and granulated to obtain a PA hot melt adhesive material for low-pressure injection molding.

[0095] Example 2

[0096] This embodiment provides a PA hot melt adhesive material for low-pressure injection molding, comprising the following raw materials in parts by weight: 295 parts of carboxylic acid monomer prepared in Preparation Example 5, 55 parts of suberic acid, 94 parts of hexamethylenediamine, 27 parts of dodecanediamine, 1.4 parts of paraffin, 0.35 parts of benzoic acid, 5.8 parts of azobisisoheptonitrile and 5.5 parts of functionalized filler prepared in Preparation Example 8;

[0097] The preparation method of the PA hot melt adhesive material used for low-pressure injection molding comprises the following steps:

[0098] Step S1, preparation of prepolymer: carboxylic acid monomer, suberic acid, hexamethylenediamine, dodecanediamine and 2 / 3 parts by weight of azobisisoheptanenitrile were stirred at a speed of 780 rpm for 0.50 h until uniform, heated to 63° C., maintained at a constant speed, stirred for reaction for 2.5 h to obtain an acid-amine mixture, and continued to heat to 140° C. for polycondensation reaction for 1.1 h to obtain a prepolymer;

[0099] Step S2, preparation of hot melt adhesive material: paraffin and benzoic acid are added to the prepolymer prepared in step S1, and the speed is controlled to be 840 rpm and stirred for 0.65 h until uniform, and the speed is maintained unchanged, and the temperature is continued to be raised to 242 ° C., and the reaction is stirred for 1.1 h, and the temperature is lowered to 60 ° C., and the remaining mass parts of azobisisoheptanonitrile are added, and then the functional filler is added, and the stirring is continued for 2.8 h. Cool, granulate, and obtain PA hot melt adhesive material for low-pressure injection molding.

[0100] Example 3

[0101] This embodiment provides a PA hot melt adhesive material for low-pressure injection molding, comprising the following raw materials in parts by weight: 320 parts of carboxylic acid monomer prepared in Preparation Example 6, 60 parts of suberic acid, 116 parts of hexamethylenediamine, 36 parts of dodecanediamine, 1.6 parts of paraffin wax, 0.4 parts of benzoic acid, 6.2 parts of azobisisobutyronitrile and 7 parts of functional filler prepared in Preparation Example 9;

[0102] The preparation method of the PA hot melt adhesive material used for low-pressure injection molding comprises the following steps:

[0103] Step S1, preparation of prepolymer: carboxylic acid monomer, suberic acid, hexamethylenediamine, dodecanediamine and 2 / 3 parts by weight of azobisisobutyronitrile were stirred at a speed of 810 rpm for 0.55 h until uniform, heated to 64° C., stirred for reaction for 3 h to obtain an acid-amine mixture, and continued to heat to 144° C., polycondensed for 1.6 h to obtain a prepolymer;

[0104] Step S2, preparation of hot melt adhesive material: paraffin and benzoic acid are added to the prepolymer prepared in step S1, and the speed is controlled to be 860 rpm and stirred for 0.7 h until uniform, and the temperature is continued to rise to 245 ° C., and the speed is maintained unchanged, and the reaction is stirred for 1.4 h. The temperature is lowered to 65 ° C., the remaining mass parts of azobisisobutyronitrile are added, and then the functional filler is added, and the stirring is continued for 3.2 h. Cool, granulate, and obtain PA hot melt adhesive material for low-pressure injection molding.

[0105] Comparative Example 1

[0106] This comparative example provides a PA hot melt adhesive material for low-pressure injection molding, comprising the following raw materials in parts by weight: 270 parts of carboxylic acid monomer prepared in Comparative Preparation Example 2, 50 parts of suberic acid, 72 parts of hexamethylenediamine, 18 parts of dodecanediamine, 1.2 parts of paraffin, 0.3 parts of benzoic acid, 5.4 parts of azobisisobutyronitrile and 4 parts of functionalized filler prepared in Preparation Example 7;

[0107] The preparation method of the PA hot melt adhesive material used for low-pressure injection molding comprises the following steps:

[0108] Step S1, preparation of prepolymer: carboxylic acid monomer, suberic acid, hexamethylenediamine, dodecanediamine and 2 / 3 parts by weight of azobisisobutyronitrile were stirred at a speed of 750 rpm for 0.45 h until uniform, heated to 62° C., maintained at a constant speed, stirred for reaction for 2 h to obtain an acid-amine mixture, and continued to heat to 136° C., maintained at a constant speed, and polycondensed for 0.6 h to obtain a prepolymer;

[0109] Step S2, preparation of hot melt adhesive material: paraffin and benzoic acid are added to the prepolymer prepared in step S1, and the speed is controlled to be stirred at 820 rpm for 0.6 h until uniform, and the temperature is continued to rise to 239 ° C., the speed is maintained unchanged, and the reaction is stirred for 0.8 h. The temperature is lowered to 55 ° C., the remaining mass parts of azobisisobutyronitrile are added, and then the functional filler is added. The stirring is continued for 2.4 h, cooled, and granulated to obtain a PA hot melt adhesive material for low-pressure injection molding.

[0110] Comparative Example 2

[0111] This comparative example provides a PA hot melt adhesive material for low-pressure injection molding, comprising the following raw materials in parts by weight: 270 parts of the carboxylic acid monomer prepared in Comparative Preparation Example 3, 50 parts of suberic acid, 72 parts of hexamethylenediamine, 18 parts of dodecanediamine, 1.2 parts of paraffin wax, 0.3 parts of benzoic acid, 5.4 parts of azobisisobutyronitrile and 4 parts of the functionalized filler prepared in Preparation Example 7;

[0112] The preparation method of the PA hot melt adhesive material used for low-pressure injection molding comprises the following steps:

[0113] Step S1, preparation of prepolymer: carboxylic acid monomer, suberic acid, hexamethylenediamine, dodecanediamine and 2 / 3 parts by weight of azobisisobutyronitrile were stirred at a speed of 750 rpm for 0.45 h until uniform, heated to 62° C., maintained at a constant speed, stirred for reaction for 2 h to obtain an acid-amine mixture, and continued to heat to 136° C., maintained at a constant speed, and polycondensed for 0.6 h to obtain a prepolymer;

[0114] Step S2, preparation of hot melt adhesive material: paraffin and benzoic acid are added to the prepolymer prepared in step S1, and the speed is controlled to be stirred at 820 rpm for 0.6 h until uniform, and the temperature is continued to rise to 239 ° C., the speed is maintained unchanged, and the reaction is stirred for 0.8 h. The temperature is lowered to 55 ° C., the remaining mass parts of azobisisobutyronitrile are added, and then the functional filler is added. The stirring is continued for 2.4 h, cooled, and granulated to obtain a PA hot melt adhesive material for low-pressure injection molding.

[0115] Comparative Example 3

[0116] This comparative example provides a PA hot melt adhesive material for low-pressure injection molding, comprising the following raw materials in parts by weight: 270 parts of the carboxylic acid monomer prepared in Preparation Example 4, 50 parts of suberic acid, 72 parts of hexamethylenediamine, 18 parts of dodecanediamine, 1.2 parts of paraffin, 0.3 parts of benzoic acid, 5.4 parts of azobisisobutyronitrile and 4 parts of the functionalized filler prepared in Comparative Preparation Example 4;

[0117] The preparation method of the PA hot melt adhesive material used for low-pressure injection molding comprises the following steps:

[0118] Step S1, preparation of prepolymer: carboxylic acid monomer, suberic acid, hexamethylenediamine, dodecanediamine and 2 / 3 parts by weight of azobisisobutyronitrile were stirred at a speed of 750 rpm for 0.45 h until uniform, heated to 62° C., maintained at a constant speed, stirred for reaction for 2 h to obtain an acid-amine mixture, and continued to heat to 136° C., maintained at a constant speed, and polycondensed for 0.6 h to obtain a prepolymer;

[0119] Step S2, preparation of hot melt adhesive material: paraffin and benzoic acid are added to the prepolymer prepared in step S1, and the speed is controlled to be stirred at 820 rpm for 0.6 h until uniform, and the temperature is continued to rise to 239 ° C., the speed is maintained unchanged, and the reaction is stirred for 0.8 h. The temperature is lowered to 55 ° C., the remaining mass parts of azobisisobutyronitrile are added, and then the functional filler is added. The stirring is continued for 2.4 h, cooled, and granulated to obtain a PA hot melt adhesive material for low-pressure injection molding.

[0120] Comparative Example 4

[0121] This comparative example provides a PA hot melt adhesive material for low-pressure injection molding, comprising the following raw materials in parts by weight: 270 parts of the carboxylic acid monomer prepared in Preparation Example 4, 50 parts of suberic acid, 72 parts of hexamethylenediamine, 18 parts of dodecanediamine, 1.2 parts of paraffin wax, 0.3 parts of benzoic acid, 5.4 parts of azobisisobutyronitrile and 4 parts of the functionalized filler prepared in Comparative Preparation Example 5;

[0122] The preparation method of the PA hot melt adhesive material used for low-pressure injection molding comprises the following steps:

[0123] Step S1, preparation of prepolymer: carboxylic acid monomer, suberic acid, hexamethylenediamine, dodecanediamine and 2 / 3 parts by weight of azobisisobutyronitrile were stirred at a speed of 750 rpm for 0.45 h until uniform, heated to 62° C., maintained at a constant speed, stirred for reaction for 2 h to obtain an acid-amine mixture, and continued to heat to 136° C., maintained at a constant speed, and polycondensed for 0.6 h to obtain a prepolymer;

[0124] Step S2, preparation of hot melt adhesive material: paraffin and benzoic acid are added to the prepolymer prepared in step S1, and the speed is controlled to be stirred at 820 rpm for 0.6 h until uniform, and the temperature is continued to rise to 239 ° C., the speed is maintained unchanged, and the reaction is stirred for 0.8 h. The temperature is lowered to 55 ° C., the remaining mass parts of azobisisobutyronitrile are added, and then the functional filler is added. The stirring is continued for 2.4 h, cooled, and granulated to obtain a PA hot melt adhesive material for low-pressure injection molding.

[0125] Performance Testing

[0126] The performance of the hot melt adhesive materials prepared in Examples 1-3 and Comparative Examples 1-4 was tested;

[0127] Specifically, it includes softening point, viscosity, low temperature resistance, tensile strength, shear strength, bonding strength and molding shrinkage; wherein, the softening point is measured according to the standard GB / T 4507-1984; the viscosity is measured according to the standard GB / T 2794-1995, using a rotational viscometer, and the heating temperature is 220°C; the low temperature resistance is tested according to the standard ASTM-D746-2004; the tensile strength is measured according to the standard GB / T528-1998; the shear strength is measured according to GB 7124-1986, wherein PA hot melt adhesive material is applied to the clean copper foil surface; the bonding strength is tested according to ASTM-D1876-72, and the molding shrinkage is tested according to the standard GB / T 15585-1995. The specific test data are recorded in Table 1;

[0128] Table 1. Performance test of hot melt adhesives prepared in Examples 1-3 and Comparative Examples 1-4

[0129]

[0130] It can be seen from Table 1 that, compared with Comparative Examples 1-4, the hot melt adhesive prepared in Examples 1-3 has a higher melting point, more excellent mechanical properties and better anti-shrinkage performance.

[0131] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.

Claims

1. A PA hot melt adhesive material used for low pressure injection molding, characterized in that: The method comprises the following raw materials in parts by weight: 270-320 parts of carboxylic acid monomer, 50-60 parts of suberic acid, 72-116 parts of hexamethylenediamine, 18-36 parts of dodecanediamine, 1.2-1.6 parts of paraffin wax, 0.3-0.4 parts of benzoic acid, 5.4-6.2 parts of free radical initiator and 4-7 parts of functionalized filler; The carboxylic acid monomer is prepared by the following steps: Step A1, under nitrogen protection, add the esterification monomer and undecylenic acid to anhydrous tetrahydrofuran, stir evenly, heat to 35-45°C, and add dropwise to the mixed solution a of p-toluenesulfonic acid and anhydrous tetrahydrofuran while stirring, and control the dripping to be completed within 10 minutes. After the dripping is completed, continue stirring for 3-5 hours, then heat to reflux, continue stirring to react for 8-12 hours. After the reaction is completed, filter by suction, wash and dry the filter cake to obtain an unsaturated monomer, wherein the mass ratio of the esterification monomer, undecylenic acid, anhydrous tetrahydrofuran and the mixed solution a is 1.5-2.3:1:30-40:18-22, and the mass ratio of p-toluenesulfonic acid and anhydrous tetrahydrofuran in the mixed solution a is 0.2-0.6:22-26; Step A2, adding unsaturated monomer, 2,2-dimethylsuccinic anhydride and 4-dimethylaminopyridine to anhydrous tetrahydrofuran, stirring evenly, heating to reflux, continuing stirring to react for 16-20h, then adding a mixed solution b of deionized water and anhydrous tetrahydrofuran, and then adding dichloromethane, washing, rotary evaporation, and drying to obtain a carboxylic acid monomer, wherein the mass ratio of the unsaturated monomer, 2,2-dimethylsuccinic anhydride, 4-dimethylaminopyridine, anhydrous tetrahydrofuran, mixed solution b and dichloromethane is 1.2-1.4:3.6-4.2:0.1-0.14:45-55:18-22:6-10, and the mass ratio of deionized water and anhydrous tetrahydrofuran in the mixed solution b is 6-10:16-20; The esterification monomer is prepared by the following steps: Add 3,5-diaminobenzoic acid, pentaerythritol allyl ether and p-toluenesulfonic acid to anhydrous N,N-dimethylformamide, stir evenly, heat to 75-85°C under nitrogen protection, stir and react for 18-20 hours, stand for 4-6 hours after the reaction, filter, wash and dry the filter cake to obtain an esterification monomer, wherein the mass ratio of 3,5-diaminobenzoic acid, pentaerythritol allyl ether, p-toluenesulfonic acid and anhydrous N,N-dimethylformamide is 1:2-3:0.06-0.08:35-45; The functionalized filler is prepared by the following steps: Step B1, 4,4'-diaminodiphenyl disulfide, deionized water, anhydrous ethanol and KH-560 are mixed evenly, heated to 76-80°C, stirred and reacted for 10-14 hours, centrifuged, precipitated, washed and dried to obtain an amino monomer, wherein the mass ratio of 4,4'-diaminodiphenyl disulfide, deionized water, anhydrous ethanol and KH-560 is 1.2-1.8:10:20-24:0.8-1.0; Step B2, adding the amino monomer to anhydrous DMF, heating to 45-55°C, stirring evenly, adjusting the pH to 9-10, and dropping a mixed solution c of octadecenyl succinic anhydride and isopropanol while stirring, and controlling the dropping to be completed within 30 minutes. After the dropping is completed, heating to 74-80°C, continuing to stir and react for 6-10 hours, adjusting the pH to neutral, and obtaining a modified solution, wherein the mass ratio of the amino monomer, anhydrous N, N-dimethylformamide and the mixed solution c is 2-4:50-60:16, and the mass ratio of octadecenyl succinic anhydride and isopropanol in the mixed solution c is 0.6-1.2:12; Step B3, ultrasonically disperse the nano-silica in anhydrous N, N-dimethylformamide, add the modifying liquid and deionized water, heat to 55-65°C, stir and react for 4-5 hours, filter, wash and dry to obtain a functionalized filler, wherein the mass ratio of nano-silica, anhydrous N, N-dimethylformamide, modifying liquid and deionized water is 6-8:65-75:16-24:8-10.

2. A method for preparing a PA hot melt adhesive material for low-pressure injection molding according to claim 1, characterized in that: The following steps are involved: Step S1, preparation of prepolymer: carboxylic acid monomer, suberic acid, hexamethylenediamine, dodecanediamine and 2 / 3 parts by weight of free radical initiator are uniformly mixed to obtain an acid-amine mixture, and the mixture is heated to 136-144° C. and subjected to polycondensation reaction for 0.6-1.6 hours to obtain a prepolymer; Step S2, preparation of hot melt adhesive material: add paraffin and benzoic acid to the prepolymer prepared in step S1, stir evenly, continue to heat to 239-245°C, continue stirring and reacting for 0.8-1.4h, cool to 55-65°C, add the remaining mass part of free radical initiator, then add functional filler, continue stirring for 2.4-3.2h, cool, and granulate to obtain PA hot melt adhesive material for low-pressure injection molding.

Citation Information

Patent Citations

  • High-viscosity two-component adhesive and preparation method thereof

    CN116445123A

  • Low-pressure injection molding copolyamide hot melt adhesive and preparation method thereof

    CN116640547A